Students' perceptions of factors affecting clinical learning - Diaz-Mojica, Ma. Georgina G. (1994)
All senior speech pathology students, seven females and one male, of the College of Allied Medical Professions, University of the Philippines Manila in their clinical internship year with ages ranging from 19-21 years old (mean = 20.25) participated in this study to 1) identify the specific dimensions that the students perceive to affect their clinical learning in terms of the following factors: clinical supervisors' attributes, students' attributes, clients/patients, clinical setting and the training program and 2) rank these perceived factors according to their importance. The students were asked to answer a 56-item questionnaire containing 50 structured questions with a 4-point rating scale and 6 open-ended questions. Data were tabulated and a comparison of the extent of agreements was done. These comparisons were interpreted using both semi-quantitative and semi-qualitative analyses. The results showed that clinical supervisors who allowed students to develop their own clinical style and provided helpful recommendations related to patient management were perceived to maximize clinical learning. In addition, the students performed better when faced with particular clinical tasks wherein they were confident of their skills. Regular attendance of therapy sessions or compliance to therapy was the most important dimension perceived regarding patient/client factors. Furthermore, clinical learning was maximized when the affiliation center provided a variety of patients to manage as well as clear expectations from the students based on the training program objectives. The above findings agree with previous reports regarding students' perceptions of clinical learning and that learning is influenced by several interrelated factors or dimensions.
Major project (Master of Health Professions Education)--University of the Philippines Manila
Keywords: Speech pathology -- Study and teaching (Residency)